Religious issues in Malaya: a study of views and debates in Saudara, 1928-41 - Wan Sulong, Wan Suhana (IDOSI, 2011)
Saudara, published from 1928-41 was one of the major Malay newspapers in Malaya in the all-important decade before the Second World War. Influenced by Islamic reformism fervour, this newspaper became an important medium for the Malays to voice out their views on various issues. This paper will show that throughout this period, religious issues are among the central themes which dominated the contents of Saudara. Within the published pages, readers could find views and debates on religious issues such as the conflict between Kaummuda and kaumtua; bid’ah practices among the Malays;Muhammadan Law in Malaya; the establishment of Malayan Ulama Association; Lebaipondok, etc.This paper will, in other words, illustrates the religious issues which dominated the lives of the Malay people in Malaya during that time and how it is comparable to the current Malay society in Malaysia. With Saudara’s association to Islamic reformist movement in Malaya, this paper will also shed some light on how far Islamic reformism influenced the ideas and views on the debated issues.Finally, the religious issues raised in Saudara, ranging from what were considered important to more trivial ones, were by no means exclusive to the respective period, they are in fact ongoing issues which have survived through several decades and continue to have relevance in contemporary Malay society.